PENGARUH PENERAPAN MEDIA “GOOGLE EARTH” BERBASIS MODEL PEMBELAJARAN PROBLEM BASE LEARNING UNTUK MENINGKATKAN BERFIKIR SPASIAL SISWA PADA MATA PELAJARAN GEOGRAFI DI SMA N 2 PARIAMAN - Yurni Suasti; Mutiara Indah Shafira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of Google Earth learning media on the spatial thinking ability of students of SMAN 2 Pariaman. The research method used in this research is Experimental Method. Sampling was done by purposive sampling technique. The samples in this study were students of class XI.F 1 as the experimental class given the treatment of Google Earth application learning media and class XI. F3 as a control that was treated with Map learning media. Data collection using pretest and posttest instruments in the form of multiple choice that has been tested for validity and reliability, and observation. The result of this study is that there is an effect of Google Earth Learning Media on the spatial thinking ability of students in class XI. F1 SMAN 2 Pariaman. The average posttest of the experimental class was 91 and the control class was 81.39. Data analysis using the Paired Sample T-Test test from the calculated data obtained a significance level (Sig.) of 0.001 because the significance is smaller than 0.005 (0.001 <0.005), then Ho is rejected and Ha is accepted.